The Impact of Social Media Marketing on Luxury Purchase Intention: Consumer Survey in China - Ye, Jiaqi (Transactions on Economics, Business and Management Research, 2024)
The main objective of this very detailed and in-depth study is to explore how social media marketing strategies significantly influence consumers’ willingness and propensity to purchase these expensive luxury goods. This very important and systematic study was conducted in China, using a scientific research methodology based on rigorous quantitative methods, with reliable data collected through a well-designed, nuanced and comprehensive online questionnaire. The study used a variety of sophisticated and scientific statistical analysis techniques such as validity and reliability tests, correlation assessment, and regression analysis. The results showed a Cronbach’s alpha coefficient of 0.7097, which indicates a high level of consistency and reliability of the collected data. Meanwhile, the factor analysis also confirmed the validity and representativeness of the sample data, supporting hypothesis H1a. Hence, luxury brands in the Chinese market should pay more attention to their social medial marketing strategies in the future to increase Chinese consumers’ purchasing intention, improving their performance in the Chinese market.